An Integral Model of Collective Action in Organizations and Beyond - Tang, Lu (Journal of business ethics, 2008)
While a large amount of work has been done to understand public good and to construct conceptual models explaining the antecedents of collective action, current literature is flawed in that most of them only examine the lower-level public good and attribute people's participation in collective action to external variables. It pays little to the developmental nature of collective action. Utilizing Ken Wilber's theory of integral psychology, this paper proposes a holistic definition of public good, emphasizing its different levels of development. The paper also introduces an integral model of collective action that explains the antecedents of collective action in terms of not only the external individual behavior and social factors but also the internal aspects of individuals, organization, and society.